2021
DOI: 10.18585/inabj.v13i1.1406
|View full text |Cite
|
Sign up to set email alerts
|

Splice-site and Frameshift Mutations of β-Globin Gene Found in Thalassemia Carrier Screening in Yogyakarta Special Region, Indonesia

Abstract: BACKGROUND: β-thalassemia is an inherited blood disorder that relatively common in Southeast Asian countries. In Indonesia, it is estimated that 200,000 infants with thalassemia carrier born each year. Mutation causing β-thalassemia is highly varied and relatively specific in a population. This study aimed to identify the mutations responsible for β-thalassemia from Thalassemia Carrier Screening conducted in Yogyakarta Special Region. This information is beneficial for developing a strategic prevention program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The results of our study are also comparable to a recent study reported in Yogyakarta Special Region, conducted on 28 patients which showed six (6) β-globin gene mutations with IVS-1-5 (G>C) being the most dominant (71.4%) (13).…”
Section: Discussionsupporting
confidence: 91%
“…The results of our study are also comparable to a recent study reported in Yogyakarta Special Region, conducted on 28 patients which showed six (6) β-globin gene mutations with IVS-1-5 (G>C) being the most dominant (71.4%) (13).…”
Section: Discussionsupporting
confidence: 91%
“…(3) β-thalassemia is defined as a quantitative defect in production of β-globin chains due to mutation on β-globin (HBB) gene. (4,5) In attempt to simplify mass screening procedure, several indices using blood cell count parameters have been introduced to discriminate microcytic anemia due to β-thalassemia carrier (BTC) or iron deficiency (6) since iron deficiency anemia (IDA) is also common in Indonesia (7).…”
Section: Introductionmentioning
confidence: 99%